Effects of environmental stress on forest crown condition in Europe. Part II: Estimation of stress induced by meteorology and air pollutants - Leeuwen, E. P. Van; Hendriks, KCMA (Water, Air, & Soil Pollution, 2000)
In order to assess the relationship between environmental stress and crown condition of forest trees monitored since 1986 in Europe, estimates of stress factors, including temperature stress, drought stress and air pollution stress, were derived with the best data, methods and models currently available. This paper presents information on the methods used to derive such stress factors, and on the overall ranges, the temporal trends, the spatial distribution and the reliability of the calculated stress factors. The temperature stress indices did not show much temporal variation between 1985 to 1995. As expected spatial patterns were north-south orientated, going from colder northern regions to warmer southern regions. The calculated relative transpiration showed a more complex pattern, coinciding to a large extend with patterns of rainfall and temperature. Potential acid deposition decreased between 1986 and 1992, but remained fairly constant after 1992. The strong decrease was mainly the result of the decrease in SOx deposition, and to a small decrease in NOy deposition. Highest levels of the S and N deposition were calculated in Central and Western Europe. Base cation deposition was largest in coastal areas and in southern Europe. This is mainly due to soil dust, Sahara dust and sea salt. Base cation deposition can compensate almost entirely for the potential inputs in the south of Europe, whereas in central Europe it equalled about 25% of the potential acid input. A comparison between site speciﬁc modelled deposition and deposition derived from throughfall data showed that the total acid deposition is usually overestimated by the model, whereas the total nitrogen deposition is underestimated, especially at plots with high nitrogen loads. There is, however, a signiﬁcant correlation between measured and modelled data for all S and N deposition, thus allowing their use in a statistical analyses.
Keywords: acidity; air pollution; ammonia; atmospheric deposition; Base cations; deposition model; Drought; nitrogen oxides; Ozone; sulphur; temperature stress; water balance

metal contents in Parmelia caperata(L.) Ach. compared to bulk deposition, throughfall and leaf-wash fluxes in two holm oak forests in Montseny (NE Spain) - Rodrigo, A.; Avila, A.; Gómez-Bolea, A. (Atmospheric Environment, 1999)
The metal concentrations of V, Cr, Co, Ni, Cu, Zn, Cd, Hg and Pb were analysed in distilled water extracts of Parmelia caperata and in bulk deposition, throughfall and an experimental in situ washing of leaves at two forests at Montseny (NE Spain) submitted to di¤erential exposure to the industrial and tra¦c activities around Barcelona. Lichen concentra- tions of Zn, Cu, V, and Cd were higher at the site of greater exposure to pollutants. Consistently, there was higher dry deposition of these metals at the more exposed site. The order of abundance of trace metals in the lichen was similar to that in the deposition variables, although Pb and Cu had intermediate concentrations in the lichen but were very low in the deposition measurements. This indicated the higher a¦nity of Pb and Cu for the exchange sites in the lichen cell wall and the fact that lichens accumulated Pb for the last 12Ð18 y when emissions were much higher than today. The ability of Parmelia caperata to indicate the deposition of heavy metals, together with its easy sampling and handling, its broad distribution and its easy identiÞcation suggest that the lichen extract procedure described here could be used to establish gradients of atmospheric deposition of heavy metals at a general geographic level
Keywords: atmospheric deposition; bulk deposition; parmelia caperata; Quercus ilex; throughfall; trace metal

metal contents in Parmelia caperata(L.) Ach. compared to bulk deposition, throughfall and leaf-wash fluxes in two holm oak forests in Montseny (NE Spain) - Rodrigo, a; Avila, a; Gómez-Bolea, A (Atmospheric Environment, 1999)
The metal concentrations of V, Cr, Co, Ni, Cu, Zn, Cd, Hg and Pb were analysed in distilled water extracts of Parmelia caperata and in bulk deposition, throughfall and an experimental in situ washing of leaves at two forests at Montseny (NE Spain) submitted to di¤erential exposure to the industrial and tra¦c activities around Barcelona. Lichen concentra- tions of Zn, Cu, V, and Cd were higher at the site of greater exposure to pollutants. Consistently, there was higher dry deposition of these metals at the more exposed site. The order of abundance of trace metals in the lichen was similar to that in the deposition variables, although Pb and Cu had intermediate concentrations in the lichen but were very low in the deposition measurements. This indicated the higher a¦nity of Pb and Cu for the exchange sites in the lichen cell wall and the fact that lichens accumulated Pb for the last 12Ð18 y when emissions were much higher than today. The ability of Parmelia caperata to indicate the deposition of heavy metals, together with its easy sampling and handling, its broad distribution and its easy identiÞcation suggest that the lichen extract procedure described here could be used to establish gradients of atmospheric deposition of heavy metals at a general geographic level
Keywords: atmospheric deposition; bulk deposition; parmelia caperata; Quercus ilex; throughfall; trace metal

Modelling the long-term impacts of atmospheric pollution deposition and repeated forestry cycles on stream water chemistry for a holm oak forest in northeastern - Neal, C; Avila, a; Rodà, F (Journal of Hydrology, 1995)
Estimates based on the MAGIC model of the long-term effects on stream water quality of forest management cycles as well as of atmospheric pollutant inputs for a holm oak catchment in northeastern Spain, show that despite high pollutant sulphur inputs as well as substantial base cation loss from the catchment owing to forest harvesting, stream water has not deteriorated in any major way. Acidification of the catchment will continue, to a limited degree, unless either sulphur deposition is reduced by more than 60% or forest harvesting schemes are terminated. The detrimental changes in water quality owing to acid deposition and forestry harvesting practice in other parts of Europe are not observed in this region, because of high base inputs from the atmosphere and high base cation weathering rates within the catchment.
Keywords: atmospheric deposition; forestry practices (voyant); pollution; soil chemistry; stream water chemistry